The Influence of Auditor Experience, Interpersonal Skills, and Competence on the Quality of Consultation Provided by BPKP - Muhammad Wahyu Adhi Pratama (Institut Manajemen Wiyata Indonesia, 2026)
Internal auditors, as consultants, are expected to minimize fraud. As such, this study aims to seek empirical evidence of the positive effect of auditor experience, interpersonal skills, and competence on the consulting quality of BPKP. BPKP auditors are selected as the population in the study for their consulting function in addition to its coaching function for the Government Internal Audit (APIP). The samples include 126 auditors, and the data are analyzed by multiple regression. The research findings exhibit that auditor experience has no effect on their consulting quality whilst interpersonal skills and competence have a positive effect on their consulting quality. This research is expected to provide empirical evidence to improve the interpersonal skills and competence of auditors.